(untitled) (Agroindustria, Sociedad y Ambiente, 2016)
This work is framed in a quantitative research, based on a design of field research, descriptive level, for the purpose of describing the participation of student organized group Majokaraisa Program Higher Agricultural Technology UCLA in promoting Environmental Education in the Curarigua community in the municipality Torres. The study subjects were represented by twenty (28) students belonging to Majokaraisa group who were administered a questionnaire type instrument structured for forty items with three possible answers: Never Always (S) Sometimes (AV) and (N). This instrument was validated through expert judgment and statistical reliability was used Cronbach alpha coefficient, yielding a value of 0.93. The results were analyzed according to the criteria of descriptive statistics, estimating absolute and percentage frequencies and the arithmetic average of answer choices, which reflected that most students Majokaraisa manifiestaron group owning 71.43% environmental sensitivity and 92 86% have high concern for developing environmentally focused projects that help preserve the environment. Also, active in the promotion of environmental education to help environmental conservation and integrate Curarigua community in solving social and environmental problems in the environment where they make active life.